A NEW APPROACH TO TREATING OBESITY: INTEGRATING ADVANCED PHARMACOTHERAPY AND METABOLIC SURGERY IN A PERSONALISED TREATMENT ALGORITHM - Katarzyna Kleszczewska; Agnieszka Pruska; Natalia Senatorska; Julia Rarok; Daria Godlewska; Hanna Pietruszewska; Monika Banaszek; Agata Panfil; Julia Błocka; Agata Lurka (International Journal of Innovative Technologies in Social Science, 2025)
Background: Obesity management will need new approaches as opposed to traditional approaches that are often ineffective. The review will bring together current available evidence on the advanced pharmacotherapy and metabolic surgery to mend this treatment gap.Methods: PubMed, Scopus, and Web of Science (2020-2024) were used to search for and find a narrative review. These trials, meta-analyses, and consensus publications on GLP-1 receptor agonists (e.g., semaglutide, tirzepatide) and metabolic interventions (e.g., gastric bypass, sleeve gastrectomy) were combined and analyzed by us.Results: New pharmacotherapies increase weight loss by 1522 per weight loss, matching the effect of surgical procedures and providing a wide range of cardiometabolic advantages. Yet, on discontinuation, weight regain is expected. Metabolic surgery is the most permanent operation, and it maintains weight reduction of 25-35 per cent for more than 10 years and determines significant remission of type 2 diabetes. The two modalities are complementary in that pharmacotherapy offers a definitive solution that is scalable and reversible, whereas surgery offers a definitive physiological solution. We combine these results and come up with a personalised algorithm of treatment that incorporates both of them, depending on the severity of the disease and the factors related to the patient.Conclusion: The future of effective and individualized management of obesity relies on an integrated and chronic care model that should be deployed in the pharmacotherapy and surgery combination in a synergistic way.